Analisis Pengendalian Kualitas Produk Keripik Pisang UMKM My Kripis Menggunakan Metode Fishbone dan Check Sheet - Nadia Febriani Siti Awaliyyah; Aghitsni Nailalmuna; Salwa Syahira; Nabilah Putri; Debora K.P; Dessy Damayanthy (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study was conducted to evaluate the quality of banana chips products at My Kripis by using the Check Sheet and Fishbone Diagram methods. The main problem found was the high rate of defective products, which reached 3.79% of the total monthly production. The largest type of defect was recorded as inappropriate banana ripeness during the frying process, which amounted to 18 kg out of a total of 37.2 kg of defective products. Data was collected through direct observation and interviews, then analyzed using an inspection sheet to identify the type and frequency of defects. Results showed that the dominant cause of defective products came from raw material factors, such as non-uniform banana ripeness and inconsistent slice thickness. A Fishbone Diagram was used to identify root causes from various aspects, including man, methods, machines, and materials. These findings served as the basis for recommendations to improve the production process, such as standardizing cutting procedures, training operators, and monitoring the quality of raw materials. This research confirms the importance of simple yet systematic quality control for MSMEs to sustainably improve product quality.